Assessment of the effectiveness of light-emitting diode and diode laser hybrid light sources to intensify dental bleaching treatment - Gomes Torres, Carlos Rocha [UNESP]; Barcellos, Daphne Camara; Batista, Graziela Ribeiro; Borges, Alessandra Buhler [UNESP]; Cassiano, Karla Viana; Pucci, Cesar Rogerio [UNESP] (Informa Healthcare, 2011)
Objective. To evaluate the effectiveness of the color change of hybrid light-emitting diode (LED) and low-intensity infrared diode laser devices for activating dental bleaching and to verify the occurrence of a color regression with time. Material and methods. A total of 180 specimens obtained from human premolars were immersed in a coffee solution for 15 days for darkening and then divided into eight experimental groups (n = 20 in each) as follows: G1, bleaching without light; G2, bleaching with halogen light; G3, bleaching with a blue LED (1000 mW/470 nm) and a laser device (120 mW/795 nm) simultaneously; G4, bleaching with an LED emitting blue light (1000 mW/470 nm); G5, bleaching with a blue LED (800 mW/470 nm) and a laser device (500 mW/830 nm) simultaneously; G6, bleaching with a blue LED device (800 mW); G7, bleaching with a green LED (600 mW/530 nm) and a laser device (120 mW/795 nm) simultaneously; and G8, bleaching with a green LED (600 mW). Three measurements were performed (at baseline and 14 days and 12 months after bleaching) using a Vita Easyshade spectrophotometer. The data were submitted to two-way ANOVA and a Tukey test. Results. All groups showed significantly higher Delta E values than Group G1, with the exception of Group G8. Variations in the Delta E values at 14 days were significant when compared with those obtained at baseline and after 12 months. Conclusions. Light activation of the bleaching gel provided faster and more intense bleaching than use of the bleaching gel without light activation. Combinations of low-intensity diode lasers are ineffective as a bleaching gel activator. Color regression was observed after 12 months of storage.
Keywords: Laser; light-emitting diode; tooth bleaching